2011
DOI: 10.1038/nature09658
|View full text |Cite
|
Sign up to set email alerts
|

MMSET regulates histone H4K20 methylation and 53BP1 accumulation at DNA damage sites

Abstract: p53-binding protein 1 (53BP1) is known to be an important mediator of the DNA-damage response1, with di-methylation of histone H4 lysine 20 (H4K20me2) critical to the recruitment of 53BP1 to double strand breaks (DSBs)2,3. However, it is not clear how 53BP1 is specifically targeted to the sites of DNA damage, since the overall level of H4K20me2 does not seem to increase following DNA damage. It has been proposed that DNA breaks may cause exposure of methylated H4K20 previously buried within the chromosome, how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
403
7
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 382 publications
(425 citation statements)
references
References 30 publications
10
403
7
5
Order By: Relevance
“…In addition, we measured H4K20me2 enrichment at a locus adjacent to a single I‐SceI meganuclease‐induced DSB (Fig EV4D). We could detect increased H4K20me2 levels upon DSB induction in both control and cells with SIRT7 knockdown, as has been reported previously (Pei et al , 2011). Most important, we did not observe differences of H4K20me2 levels upon SIRT7 depletion compared to control (Fig EV4E).…”
Section: Resultssupporting
confidence: 89%
“…In addition, we measured H4K20me2 enrichment at a locus adjacent to a single I‐SceI meganuclease‐induced DSB (Fig EV4D). We could detect increased H4K20me2 levels upon DSB induction in both control and cells with SIRT7 knockdown, as has been reported previously (Pei et al , 2011). Most important, we did not observe differences of H4K20me2 levels upon SIRT7 depletion compared to control (Fig EV4E).…”
Section: Resultssupporting
confidence: 89%
“…26,27 Histone modification is essential for the establishment and maintenance of transcriptional programs during development and gene dosage alterations of histone modifiers are a known cause of intellectual disability syndromes. 28 The HMT function of WHSC1 has been implicated in diverse biological processes, including early development, 29 cytokine signaling, 30 the DNA damage response 31,32 and class switch recombination. 33 In addition to its functional diversity, WHSC1 has a complex pattern of expression, with the potential to regulate multiple processes during development.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the lysine methyltransferase MMSET is recruited to DNA breaks to locally increase the amount of methylated H4K20 [13]. However, the MMSET-mediated methylation of H4K20 or its localization to DNA breaks is not dependent on RNF8 activity [13]. Hence, the local enrichment of H4K20(me2) triggered by MMSET does not explain the requirement of RNF8 for the recruitment of 53BP1 [5][6][7].…”
mentioning
confidence: 97%
“…Nucleosome stacking may contribute to bury methylated H4K20, but since nucleosomes are highly dynamic structures, even buried sites become accessible for protein binding. It was shown that the lysine methyltransferase MMSET is recruited to DNA breaks to locally increase the amount of methylated H4K20 [13]. However, the MMSET-mediated methylation of H4K20 or its localization to DNA breaks is not dependent on RNF8 activity [13].…”
mentioning
confidence: 99%